PENGUJIAN AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) TERHADAP BAKTERI PENYEBAB INFEKSI SALURAN PENCERNAAN MENGGUNAKAN METODE DIFUSI AGAR - Fitriana, Fitriana; Asmaliani, Ira; Ar Ridwan, Yuki Ayumi (As-Syifaa Jurnal Farmasi, 2024)
Dayak onion leaves (Eleutherine palmifolia (L.) Merr) possess various biological activities, including antibiotic, antiviral, anti-inflammatory, and antibacterial properties, attributed to their secondary metabolites such as flavonoids, saponins, tannins, and phenolics. This study aimed to determine the antibacterial activity of ethanol extract from Dayak onion leaves against gastrointestinal infection-causing bacteria. The research began with screening tests of ethanol extract at concentrations of 0.1%, 0.5%, and 1% against Escherichia coli, Shigella dysenteriae, Vibrio cholerae, and Salmonella typhi. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using extract concentrations of 1%, 2%, 4%, 8%, and 16%. Antibacterial activity was evaluated using the agar diffusion method at concentrations of 5%, 10%, and 15%. Screening results indicated antibacterial activity at a 1% concentration against all tested bacteria. The MIC value for all bacteria was 2%, while the MBC was 1% for Vibrio cholerae and 2% for Escherichia coli, Salmonella typhi, and Shigella dysenteriae. The agar diffusion method revealed the largest inhibition zones at a 15% concentration, with diameters of 10.23 mm for E. coli, 10.31 mm for S. dysenteriae, 11.07 mm for V. cholerae, and 11.32 mm for S. typhi. These findings indicate the potential of ethanol extract from Dayak onion leaves as an antibacterial agent.